Cultivating positive values via online project-based module (M-Pat) / Ashfahani Zakaria … [et al.] - Zakaria, Ashfahani; Mohd. Salleh, Amla; Ismail, Mohd. Arif; Ghavifekr, Simin (Research Management Centre (RMC), 2019)
The purpose of this paper is to evaluate the use of the Online Project-based module (m-PAT) to cultivate positive values among students. Evaluation was made to the positive values used in this study based on the six constructs of Contextual Development Model for Positive Youth Development namely competence, confidence, connection, caring, character and contribution (6C’s). The learning approach used by m-PAT is project-based learning which is applied as a School Based Assessment activity for Physics subject. A mixed method case study design was employed, where the findings of quantitative data were confirmed using the findings of qualitative data. A total of 42 Form 4 students were chosen based on purposive sampling from a secondary school in Klang Valley, Malaysia. The data were collected through questionnaire, student reflection, students’ online learning activity and discussion, interviews with the students, as well as teacher’s checklist after each participant generated a physic-learning blog by using the m-PAT as a platform. Quantitative data were analysed descriptively in form of mean scores and standard deviations to observe the distribution of students’ feedback on the constructs being studied. Qualitative data were analysed using thematic analysis related to the constructs being studied and confirmed by teacher’s checklist. The results showed that m-PAT was able to cultivate all positive values of 6C’s among the participants of the study. Overall, the findings has important implications for contributing to a new approach in learning which integrates the use of information technology and communication via project-based online learning as well as making it possible for the cultivation of students’ positive values especially in relation to the use of the Internet. Further research with a larger number of participants is needed to support the present findings.